Physicochemical and bacteriological characterization of white artisan cheese in Buria parish, Lara state, Venezuela. (Gaceta de Ciencias Veterinarias, 2016)
Artisan white cheeses represent a potential risk to cause foodborne illness, due to poor sanitary conditions processing; routinely using unpasteurized Milk makes these products become in vehicles for infectious pathogens. In order to evaluate the physical, chemical and bacteriological quality of fresh artisan cheeses, applying methodology established in Venezuelan COVENIN, 32 samples were analyzed from eight artisanal cheese making production units (UP) milk included in the Dairy Development Integrated Program (PIDEL) in Manzanita, Buría parish, Lara state. The data were statistically evaluated by ANOVA (P
Keywords: Cheese; bacteriological quality; pathogens in food